The Night of the Shooting Stars - Nuit de San Lorenzo, La - Paolo Taviani, Vittorio Taviani (1982)
The Night of San Lorenzo, the night of the shooting stars, is the night when dreams come true in Italian folklore. In 1944, a group of Italians flee their town after hearing rumours that the Nazis plan to blow it up and that the Americans are about to arrive to liberate them.
Keywords: Drama, Romance, War